2018
DOI: 10.1080/07420528.2018.1466792
|View full text |Cite
|
Sign up to set email alerts
|

Permanent night workers´ sleep and psychosocial factors in hospital work. A comparison to day and shift work

Abstract: We aimed to study whether permanent night workers sleep and psychosocial factors differ from day workers and shift workers. The participants (n = 9 312, 92% females, average age 45 years, most commonly nurses and departmental secretaries) were day workers (DW, n = 2 672), shift workers (SW, n = 6 486) and permanent night workers (PNW, n = 154). The Finnish Public Sector survey responses from six hospital districts from 2012 were combined to payroll data from 91 days preceding the survey. The data were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 35 publications
0
11
1
Order By: Relevance
“…However, studies from the Finnish Public Sector database demonstrated that permanent night workers manifest inconsistent differences in sleep quality compared to day and shift workers. Since a slightly longer average length of sleep, fewer problems in maintaining sleep, and more difficulties in falling asleep were observed in night workers, the authors concluded that the type of shift alone cannot explain the association between WV and SPs (Karhula et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…However, studies from the Finnish Public Sector database demonstrated that permanent night workers manifest inconsistent differences in sleep quality compared to day and shift workers. Since a slightly longer average length of sleep, fewer problems in maintaining sleep, and more difficulties in falling asleep were observed in night workers, the authors concluded that the type of shift alone cannot explain the association between WV and SPs (Karhula et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Because the ICSD‐3 specifies the reduction of total sleep time as an SWD symptom, only those ICSD‐2‐based SWD cases who answered the question ‘Do you sleep sufficiently?’ with ‘rarely or almost never’ on a four‐point scale (from ‘yes, almost always’ to ‘rarely or almost never’; Karhula et al., ) were assigned as ICSD‐3‐based SWD cases.…”
Section: Methodsmentioning
confidence: 99%
“…Such an arrangement would help avoid disruptive 'day-at-a-time' evening assignments. 39 To incentivise such an arrangement, professionals who choose steady off-hours work could be given fewer weekend or holiday assignments, for example. Admittedly, this creativity in scheduling depends on the willingness of existing and recruited faculty to adopt atypical schedules.…”
Section: Supporting Women In Anaesthesiology: Leadership Perspectivesmentioning
confidence: 99%